Orientation and Conformation of Proteins at the Air–Water Interface Determined from Integrative Molecular Dynamics Simulations and Sum Frequency Generation Spectroscopy - Alamdari, Sarah; Roeters, Steven J; Golbek, Thaddeus W; Schmüser, Lars; Weidner, Tobias; Pfaendtner, Jim (Langmuir, 2020)
Understanding the assembly of proteins at the air-water interface (AWI) informs the formation of protein films, emulsion properties, and protein aggregation. Determination of protein conformation and orientation at an interface is difficult to resolve with a single experimental or simulation technique alone. To date, the interfacial structure of even one of the most widely studied proteins, lysozyme, at the AWI remains unresolved. In this study, molecular dynamics (MD) simulations are used to determine if the protein adopts a side-on, head-on, or axial orientation at the AWI with two different forcefields, GROMOS-53a6 + SPC/E and a99SB-disp + TIP4P-D. Vibrational sum frequency generation (SFG) spectroscopy experiments and spectral SFG calculations validate consistency between the structure determined from MD and experiments. Overall, we show with strong agreement that lysozyme adopts an axial conformation at pH 7. Further, we provide molecular-level insight as to how pH influences the binding domains of lysozyme resulting in side-on adsorption near the isoelectric point of the lysozyme.